Hospital length of stay following admission for traumatic brain injury in a Canadian integrated trauma system: A retrospective multicenter cohort study. Issue 1 (January 2017) - Tardif, Pier-Alexandre; Moore, Lynne; Boutin, Amélie; Dufresne, Philippe; Omar, Madiba; Bourgeois, Gilles; Bonaventure, Paule Lessard; Kuimi, Brice Lionel Batomen; Turgeon, Alexis F.
Abstract: Background: Traumatic brain injury (TBI) is the leading cause of disability in children and young adults and costs CAD$3 billion annually in Canada. Stakeholders have expressed the urgent need to obtain information on resource use for TBI to improve the quality and efficiency of acute care in this patient population. We aimed to assess the components and determinants of hospital and ICU LOS for TBI admissions. Methods: We performed a retrospective multicenter cohort study on 11, 199 adults admitted for TBI between 2007 and 2012 in an inclusive Canadian trauma system. Our primary outcome measure was index hospital LOS (admission to the hospital with the highest designation level). Index LOS was compared to total LOS (all consecutive admissions related to the injury). Expected LOS was calculated by matching TBI admissions to all-diagnosis hospital admissions by age, gender, and year of admission. LOS determinants were identified using multilevel linear regression. Results: Geometric mean total LOS was 1 day longer than geometric mean index LOS (12.6 versus 11.7 days). Observed index and ICU LOS were respectively 4.2 days and 2.5 days longer than that expected according to all-diagnosis admissions. The six most important determinants of LOS were discharge destination, severity of concomitant injuries, extracranial complications, GCS, TBI severity, and mechanical ventilation, accounting for 80% of explained variation. Conclusions: Results of this multicenter retrospective cohort study suggest that hospital and ICU LOS for TBI admissions are 56% and 119% longer than expected according to all-diagnosis admissions, respectively. In addition, hospital LOS is underestimated when only the index visit is considered and is largely influenced by discharge destination and extracranial complications, suggesting that improvements could be achieved with better discharge planning and interventions targeting prevention of in-hospital complications. This study highlights the importance of considering TBI patients as a distinct population when allocating resources or planning quality improvement interventions.